Molecular diagnosis of patients with syndromic short stature identified by trio whole-exome sequencing - Sun, Huihui; Zhang, Geng; Li, Na; Bu, Xiangfang (Frontiers in Genetics, 2024)
Background: Short stature is a complex disorder with phenotypic and genetic heterogeneity. This study aimed to investigate clinical phenotypes and molecular basis of a cohort of patients with short stature.Trio whole-exome sequencing (Trio-WES) was performed to explore the genetic aetiology and obtain a molecular diagnosis in twenty Chinese probands with syndromic and isolated short stature.Results: Of the twenty probands, six (6/20, 30%) patients with syndromic short stature obtained a molecular diagnosis. One novel COMP pathogenic variant c.1359delC, p.N453fs*62 and one LZTR1 likely pathogenic variant c.509G>A, p.R170Q were identified in a patient with short stature and skeletal dysplasia. One novel de novo NAA15 pathogenic variant c.63T>G, p.Y21X and one novel de novo KMT2A pathogenic variant c.3516T>A, p.N1172K was identified in two probands with short stature, intellectual disability and abnormal behaviours, respectively. One patient with short stature, cataract, and muscle weakness had a de novo POLG pathogenic variant c.2863 T>C, p.Y955H. One PHEX pathogenic variant c.1104G>A, p.W368X was identified in a patient with short stature and rickets.Maternal uniparental disomy 7 (mUPD7) was pathogenic in a patient with pre and postnatal growth retardation, wide forehead, triangular face, micrognathia and clinodactyly. Thirteen patients with isolated short stature had negative results.Trio-WES is an important strategy for identifying genetic variants and UPD in patients with syndromic short stature, in which dual genetic variants are existent in some individuals. It is important to differentiate between syndromic and isolated short stature. Genetic testing has a high yield for syndromic patients but low for isolated patients.